Eurovariety 2021: 9th European Variety in University Chemistry Education Conference : 7-9 July 2021, Ljubljana, Slovenia, online conference : book of abstracts - Devetak, Iztok (Pedagoška fakulteta, 2021)
Knjiga povzetkov konference 9th European Variety in University Chemistry Education Conference - Eurovariety2021, ki jo organizira Univerza v Ljubljani, Pedagoška fakulteta in Slovensko kemijsko društvo pod okriljem Evropskega kemijskega društva (EuChemS), Divizije za kemijsko izobraževanje, obsega program konference in povzetke prispevkov plenarnih predavanj, sekcijskih predavanj, delavnic ter posterskih predstavitev avtorjev iz Evrope in drugod po svetu (ZDA, Avstralija, .). Na konferenci bodo strokovnjaki obravnavali vsebine povezane s poučevanjem kemije na univerzitetni ravni. Konferenca zajema 13 tem, ki so aktualne na tem področju, od organizacije pouka na daljavo v času COVID-19 pandemije do izboljšav bolj ali manj tradicionalnih načinov (npr. predavanja in seminarsko delo, eksperimentalno delo, raziskovalno delo, projektno delo, .) poučevanja kemije na univerzitetni ravni. Vsi povzetki so bili recenzirani. Za jezikovno ustreznost povzetkov odgovarjajo avtorji sami. Knjiga bo elektronska in zastonj dostopna na spletni strani konference, izdala jo bo Univerza v Ljubljani, Pedagoška fakulteta. Knjiga povzetkov obsega 96 strani. The organizing committee, European Chemical Society, Division of Chemical Education and Slovenian Chemical Society has gone to great lengths to plan a memorable event and to ensure the presentations and content meet a high technical standard. We hope to share information, ideas and insights and above all, to learn from each other how to teach chemistry effectively at the university level in the three afternoons during the plenary lectures, the oral and poster presentations and the workshops. Taking into account the global COVID-19 pandemic, this is exclusively a virtual conference. We had been quite optimistic until a few months ago and hoped it could have been organised at least as a hybrid one. The COVID-19 situation in Slovenia has recently been improving but the decision made by the Division was that it is safer to organise the conference online only. Let us hope that in two years’ time, we will be able to meet face-to-face at our next Eurovariety conference. This conference includes a forum of researchers and university teachers in chemistry and chemical education. The programme and the book of abstracts are available online and we hope you will find the whole experience professionally challenging and informative. There are 13 topics of this conference and proposals submitted from all over the world covers them all.